Penerapan File Sharing Terpusat Menggunakan Samba Server Pada Kantor Kecamatan Ratu Samban - Rachmad Fachruddin; Sapri Sapri; Eko Prasetiyo Rohmawan (Jurnal Media Infotama, 2022)
ABSTRACT One of the file sharing systems is using samba with the Linux Ubuntu server operating system. Samba is a Linux application or tool that can be used to create file sharing. File sharing using samba can be distinguished by access rights based on the account and storage folder. Samba file sharing can be used by many users at once as well as many storage folders. In samba file sharing, you can limit the file extensions that can be stored in the folder, and limit the users who can use the folder. From a series of tests carried out on a file sharing system using samba on a linux ubuntu server it went well, according to the design and configurations applied. Starting from the installation of linux, ubuntu server, and samba, then login to each storage folder, after successfully logging in, new users can access files. Meanwhile, network users who do not have a login account can only access certain folders with read only access rights. Keywords: File Sharing, Linux and Samba